Amelia Earhart : the legend of the lost aviator - Tanaka, Shelley (Abrams Books for Young Readers, 2008)
Ever since Amelia Earhart and her plane disappeared on July 2, 1937, people have wanted to know more about this remarkable woman. Amelia Earhart follows the charismatic aviator from her first sight of an airplane at the age of ten to the last radio transmission she made before she vanished. Illustrated with original artworks, contemporary photographs, quotes, and details, this is a great introduction to the famous pilot.